Zadar Sea Organ - the Shaping of Urban Space and the Reimagining of a Mediterranean City - Kelemen, Petra (2009)
The focus of this presentation is on the Sea Organ located in the Croatian coastal town of Zadar, a work of the architect Nikola Bašić designed in 2005. The Organ is constructed in the western part of Zadar old town, as a point of dynamic interaction of man and nature, urban space and sea. In the positioning of Zadar in the Mediterranean map the Sea Organ represents an important element through which inhabitants can restore their relation to the sea. The paper examines ways in which that architectural object, awarded by the professional audience, changes the perception of Zadar urban space and encourages new ways in which the town's coast is used. Special attention is paid, on the one hand, to practices of the inhabitants of Zadar themselves, to whom the Organ offers novel ways of how to use one's home town and a new concept of living space, and on the other, to practices of tourists, since the Sea Organ has become one of the most frequented sites in the course of tourist tours. The paper is based on the documents related to the creation of the project and on interviews with the authors, as well as on presentations of the city in promotional material and in narratives of the space users. The place of the Sea Organ in the urban imagery is highlighted.